The Banff 2017 Kidney Meeting Report: Revised diagnostic criteria for chronic active T cell–mediated rejection, antibody‐mediated rejection, and prospects for integrative endpoints for next‐generation clinical trials. Issue 2 (21st January 2018) - Haas, M.; Loupy, A.; Lefaucheur, C.; Roufosse, C.; Glotz, D.; Seron, D.; Nankivell, B. J.; Halloran, P. F.; Colvin, R. B.; Akalin, Enver; Alachkar, N.; Bagnasco, S.; et al.
Abstract : The kidney sessions of the 2017 Banff Conference focused on 2 areas: clinical implications of inflammation in areas of interstitial fibrosis and tubular atrophy (i‐IFTA) and its relationship to T cell–mediated rejection (TCMR), and the continued evolution of molecular diagnostics, particularly in the diagnosis of antibody‐mediated rejection (ABMR). In confirmation of previous studies, it was independently demonstrated by 2 groups that i‐IFTA is associated with reduced graft survival. Furthermore, these groups presented that i‐IFTA, particularly when involving >25% of sclerotic cortex in association with tubulitis, is often a sequela of acute TCMR in association with underimmunosuppression. The classification was thus revised to include moderate i‐IFTA plus moderate or severe tubulitis as diagnostic of chronic active TCMR. Other studies demonstrated that certain molecular classifiers improve diagnosis of ABMR beyond what is possible with histology, C4d, and detection of donor‐specific antibodies (DSAs) and that both C4d and validated molecular assays can serve as potential alternatives and/or complements to DSAs in the diagnosis of ABMR. The Banff ABMR criteria are thus updated to include these alternatives. Finally, the present report paves the way for the Banff scheme to be part of an integrative approach for defining surrogate endpoints in next‐generation clinical trials. Abstract : The Banff consortium presents revisions to the diagnostic criteria for T cell– and antibody‐mediated kidney transplant rejection, including specific criteria for chronic active T cell–mediated rejection, plus prospects for integrative endpoints in clinical trials. See related articles on pages 321, 364, and 377 .